EXAMINING PORTRAITS OF TAX AVOIDANCE IN TRANSACTIONS AND OWNERSHIP OF CRYPTO-ASSETS IN THE POST-PANDEMIC ERA - Putu Bagus Adi Wibawa; Gede Sri Darma (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This study aims to determine the public's response to applying taxes on crypto assets transactions, the factors that cause people to complain about paying taxes on crypto assets transactions, and the level of public compliance in paying taxes on crypto assets transactions. This research was conducted on crypto asset activists selected as research informants. Interview, documentation and literature study methods carried out data collection in this study. The data analysis technique begins with data collection, reduction, presentation, analysis and conclusion. The results of the study show that (1) the response of taxpayers who are crypto asset activists shows a positive response to the application of taxation in crypto asset transactions, (2) the cause of taxpayers complaining about taxes on crypto asset transactions includes an administrative system that is still difficult for taxpayers to understand, tariffs relatively high taxes and crypto asset taxes only look at the value of crypto asset trading transactions without seeing whether investors make a profit or loss, and (3) regarding taxpayer compliance in crypto asset transactions, it can be done with detailed explanations or some more intense socialization so that taxpayers especially crypto asset activists understand how to report and it is hoped that administration is not complicated.